PERENCANAAN SISTEM PROPULSI ELEKTRIK PADA FAST PATROL BOAT 28 METER - Muhammad Ferdiansyah Wibowo; Raden Dimas Endro W; Anggara Trisna Nugraha (Proceedings Conference on Marine Engineering and its Application, 2023)
Selection of the propulsion system is one of the basic considerations in designing a ship. Toreduce fuel use, the researchers re-planned the mechanical propulsion system into an electricpropulsion system on the ship. The research object is a 28 M fast patrol boat with a speed of 25 knotsin full (MCR) conditions, 22 knots in patrol conditions and 15 knots in economical conditions. Theelectric motor used is a PRAXIS DC EMG-820d-7751 motor with 1457 kW of motor power suppliedfrom a battery that is charged from the shore port. Simulation using MatLab by modeling the motorand propeller to find the value of torque, thrust and advance speed. The power prediction between themotor and the propeller in the graph below can be seen that the motor power can match the powerrequired by the propeller in the condition of 52,388 % power and 100 % speed of the DC motor byadjusting the input voltage to the motor so that it affects the motor speed. The speed of the ship canreach 25 kNots, namely in clean hull conditions of 25 kNots and in rough hull conditions it does notmeet the speed requirement of 24 kNots